1991
DOI: 10.1080/07315724.1991.10718132
|View full text |Cite
|
Sign up to set email alerts
|

Effects of cholesterol and fat modification of self-selected diets on serum lipids and their specific fatty acids in normocholesterolemic and hypercholesterolemic humans.

Abstract: A 6-month crossover diet plan was employed to study the effects on human serum lipids of adding margarine or butter to otherwise self-selected diets that included two eggs daily. Two groups of subjects were studied: 51 free-living normocholesterolemic and 20 hypercholesterolemic (greater than 240 mg dl). Four-day diet records in each interval showed that subjects ate about 16% of total dietary fat as either butter or margarine. Blood samples taken every 6 weeks showed variable mean serum total cholesterol (SCH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1992
1992
2019
2019

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(3 citation statements)
references
References 53 publications
0
3
0
Order By: Relevance
“…It has been well established, in human (11) and animal (12)(13)(14)(15)(16) studies, that diets high in cholesterol and saturated fatty acids can significantly elevate plasma cholesterol levels and increase the risk of atherosclerosis. The hypercholesterolemia and changes in lipoproteins induced by diet are associated with the high incidence of coronary artery disease seen in the U.S. population.…”
Section: Introductionmentioning
confidence: 99%
“…It has been well established, in human (11) and animal (12)(13)(14)(15)(16) studies, that diets high in cholesterol and saturated fatty acids can significantly elevate plasma cholesterol levels and increase the risk of atherosclerosis. The hypercholesterolemia and changes in lipoproteins induced by diet are associated with the high incidence of coronary artery disease seen in the U.S. population.…”
Section: Introductionmentioning
confidence: 99%
“…Group 1 participants consumed the lean (Wagyu) beef during the first period, whereas Group 2 participants consumed the fattier commercial beef during the first period, but there was no difference between groups in weight loss (P> 0.25). Others (23)(24)(25)(26)(27). We did observe a nonsignificant depressioil in linoleic acid in those subjects consuming the Wagyu beef.…”
Section: Discussionmentioning
confidence: 99%
“…Dietary fat source has also been shown to have no effect on plasma cholesterol levels in atherosclerosis-susceptible pigeons in the absence of dietary cholesterol (Lofland et al 1961). Furthermore, human subjects consuming self-selected diets containing butter or margarine have been reported to exhibit no specific effect of consuming a butter diet on plasma cholesterol levels (Flynn et al 1991). Other studies conducted with individuals with normal lipoprotein profiles have also reported no effect of 16 : 0 on either total or LDL-cholesterol when consumed in the absence or presence of very-low-cholesterol diets (Sundram et al 1995).…”
Section: Esfect Of Dietary Fat Blends On Plasma Lipid Projlesmentioning
confidence: 99%